Japanese schoolgirl confidential how teenage girls made a nation cool - Ashcraft, Brian; Ueda, Shoko (Tokyo Tuttle Publishing, 2014)
Brian Ashcraft discusses the history and impact of the schoolgirl image on Japan's society and culture, and asks j-pop idols, along with other celebrities, film directors, historians, artists, and others to explain the trend, fashion choices, and its appeal.
Previous edition: Tokyo ; New York : Kodansha International, 2010.
Includes bibliographical references (pages 203-204) and index.
Keywords: Subculture -- Japan; Girls in popular culture -- Japan; Schoolgirls -- Japan